Indications for genetic testing in adults with focal segmental glomerulosclerosis - Melissa Pilco-Terán; Amir Shabaka; Mónica Furlano; Ana Tato Ribera; Isabel Galán Carrillo; Eduardo Gutiérrez; Roser Torra; Gema Fernández-Juárez (Nefrología (English Edition), 2025)
Focal segmental glomerulosclerosis (FSGS) is a histological pattern of injury that derives from various pathological processes that affect podocytes, resulting in loss of selectivity of the glomerular filtration membrane, proteinuria and the development of renal failure that progresses to end-stage kidney disease in a significant number of patients. The classification proposed by the 2021 KDIGO guidelines divides FSGS into four categories: primary, secondary, genetic, and FSGS of undetermined cause, thus facilitating its diagnosis and management. Genetic causes of FSGS present significant clinical variability, complicating their identification. Genetic testing is crucial to identify FSGS of genetic cause. The prevalence of genetic FSGS is significant in children and considerable in adults, highlighting the importance of early diagnosis to avoid unnecessary treatments and facilitate genetic counselling. Massive sequencing techniques have revolutionized genetic diagnosis, allowing the identification of more than 60 genes responsible for podocyte damage. This document proposes clinical recommendations for carrying out genetic studies in adults with FSGS, highlighting the need for a correct classification for adequate therapeutic planning and improvement of results in clinical trials. Resumen: La glomeruloesclerosis focal y segmentaria (GEFS) es un patrón histológico de lesión que deriva de diversos procesos patológicos que afectan a los podocitos, resultando en pérdida de selectividad del filtrado glomerular, proteinuria y desarrollando insuficiencia renal que progresa a enfermedad renal crónica terminal en un importante número de pacientes. La clasificación propuesta por las guías KDIGO, en 2021, divide la GEFS en cuatro categorías: primaria, secundaria, genética y de causa no determinada, facilitando así su diagnóstico y manejo. Las causas hereditarias de la GEFS presentan una variabilidad clínica significativa, complicando su identificación. El estudio genético es crucial para identificar la GEFS de causa genética. La prevalencia de la GEFS genética es significativa en niños y considerable en adultos, destacando la importancia del diagnóstico temprano para evitar tratamientos innecesarios y facilitar el consejo genético. Las técnicas de secuenciación masiva han revolucionado el diagnóstico genético, permitiendo la identificación de más de 60 genes responsables del daño podocitario. Este documento propone recomendaciones clínicas y patológicas para la realización de estudios genéticos en adultos con GEFS, subrayando la necesidad de una correcta clasificación para la planificación terapéutica adecuada y la mejora de los resultados en ensayos clínicos.